2019
DOI: 10.1093/mnras/stz2237
|View full text |Cite
|
Sign up to set email alerts
|

Star-forming, rotating spheroidal galaxies in the GAMA and SAMI surveys

Abstract: The Galaxy And Mass Assembly (GAMA) survey has morphologically identified a class of "Little Blue Spheroid" (LBS) galaxies whose relationship to other classes of galaxies we now examine in detail. Considering a sample of 868 LBSs, we find that such galaxies display similar but not identical colours, specific star formation rates, stellar population ages, mass-to-light ratios, and metallicities to Sd-Irr galaxies. We also find that LBSs typically occupy environments of even lower density than those of Sd-Irr ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…Previous studies of the blue spheroid (BSph) galaxies (Kannappan et al 2009;Schawinski et al 2009;Mahajan et al 2018;Moffett et al 2019) or Luminous Compact Blue (LCB) galaxies (Noeske et al 2006) revealed a population of the blue compact galaxies that found between z = 0 and z = 1, which are the candidates of the low-mass quiescent galaxy progenitor. This blue compact galaxy population is very likely to overlap with the UV compact galaxies we found here directly from the HDUV image.…”
Section: Origin and Evolution Of The Uv Compact Galaxymentioning
confidence: 99%
“…Previous studies of the blue spheroid (BSph) galaxies (Kannappan et al 2009;Schawinski et al 2009;Mahajan et al 2018;Moffett et al 2019) or Luminous Compact Blue (LCB) galaxies (Noeske et al 2006) revealed a population of the blue compact galaxies that found between z = 0 and z = 1, which are the candidates of the low-mass quiescent galaxy progenitor. This blue compact galaxy population is very likely to overlap with the UV compact galaxies we found here directly from the HDUV image.…”
Section: Origin and Evolution Of The Uv Compact Galaxymentioning
confidence: 99%
“…The final classification was determined by the majority opinion. This classification has been used in various studies, such as Kelvin et al (2014bKelvin et al ( , 2018, Agius et al (2013), Moffett et al (2019), Mahajan et al (2020), andBellstedt et al (2020).…”
Section: Sample Selectionmentioning
confidence: 99%
“…The Galaxy Zoo sample of Green Peas has generated extensive followup work as sources of Lyman-continuum leakage (Yang et al 2017, Malkan & Malkan 2021, Lyman α emission sources (Orlitová et al 2018), extreme starbursts driving global winds (Jaskot et al 2017, Bosch et al 2019, Hogarth et al 2020, and testbeds for chemical evolution scenarios at high star-formation rates (Hawley 2012, Amorín et al 2012). These compact, intense starbursts are likely related to the less massive "Little Blue Spheroids" (Moffett et al 2019).…”
Section: Galaxy Zoo: Green Peasmentioning
confidence: 99%